Stem Cells of the Aging Brain - Nicaise, Alexandra M.; Willis, Cory M.; Crocker, Stephen J.; Pluchino, Stefano (Frontiers in Aging Neuroscience, 2020)
The adult central nervous system (CNS) contains resident stem cells within specific niches that maintain a self-renewal and proliferative capacity to generate new neurons, astrocytes, and oligodendrocytes throughout adulthood. Physiological ageing is associated with a progressive loss of function and a decline in the self-renewal and regenerative capacities of CNS stem cells. In addition, the biggest risk factor for neurodegenerative diseases is age, and current in vivo and in vitro models of neurodegenerative diseases rarely take this into consideration. Therefore, combining both ageing research and appropriate interrogation of animal disease models towards the understanding of disease and age-related stem cell failure is imperative to the discovery of new therapies. This review will highlight the main intrinsic and extrinsic regulators of neural stem cell ageing and discuss how these factors impact normal homeostatic functions within the adult brain. We will consider established in vivo animal and in vitro human disease model systems, and then discuss the current and future trajectories of novel senotherapeutics that target ageing neural stem cells to ameliorate brain disease.